Selective interpret with eavesdrops for Cooperative Opportunistic Communication in mobile Ad-Hoc routing (International Journal of Scientific Research and Management (IJSRM), 2014)
It’s been shown that Cooperative Opportunistic Communication (COC) has the possibility to considerably build up the capability of wireless networks. However most of the results are restricted to single-hop wireless networks. To illustrate the advantages of COC in multi-hop wireless networks, we solve a combined optimization problem of relay node assignment and flow routing for concurrent sessions. We analyze this problem via mathematical modeling and solve it using a solution procedure predicated on the branch-and-cut framework. We design several novel components to speed up the computation time of branch-and-cut. Via numerical results, we show the considerable rate gains that may be achieved by incorporating COC in networks.